Solid Phase Extraction of Thorium and Uranium and their Separation from Lanthanides using Humic Acid Silica Gel as a Low-Cost Adsorbent - Prasetyo, Erik; Toyoda, Kazuhiro (Journal of Engineering and Technological Sciences, 2017)
Solid phase extraction and separation of thorium (Th), uranium (U) and lanthanides were achieved using a humic acid-modified silica gel (Si-HA). Adsorption capacity, effect of contact time, pH, and adsorbent dose were examined at room temperature. The maximum adsorbent capacities (pH = 3) for Th and U were 28.0 and 31.3 mg g-1, respectively. The isotherm parameters denoted that the adsorption was favorable and optimum conditions were attained within 90 min. The kinetic data conformed well to pseudo-second order and intra-particle diffusion models. The distribution coefficients of U, Th and lanthanides in EDTA, citric acid and nitric acid media signify the possible separation of each element from the others. The salinity did not significantly affect the ability of Si-HA to extract Th and U. The adsorbent stability and reusability were also assessed through four-adsorption-desorption cycles. The simplicity of the proposed separation method along with the stability of the adsorbent and high regeneration efficiency under acidic conditions demonstrated the merit of using Si-HA as a low-cost adsorbent.Â